A thermotropic glass
Patent Information
- Application Number
- CN202611141249.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]但,铜卤化物配位聚合物多为晶态或交联凝胶结构,配位键的方向性与刚性骨架使其本征脆性极强,纯相薄膜断裂伸长率通常低于2%,弯折、温度循环过程中极易产生裂纹甚至粉化脱落,无法独立成膜使用,也难以适配玻璃夹胶的高温高压加工工艺
[0016]低温状态下,Cu(I)与碘离子、吡唑氮原子形成稳定的四面体配位构型,Cu4I4簇的d-d轨道跃迁能级差较大,特征吸收峰位于紫外光区,薄膜在可见光波段高透明;当温度升高至相变区间时,热运动使配位键发生可逆畸变,Cu-Cu金属间相互作用增强,轨道能级差减小,吸收边向可见光-近红外波段红移,薄膜颜色加深、太阳辐射透射率降低;温度回落时,配位构型自发恢复,薄膜回归高透态,实现被动式智能调光。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of energy-efficient building technology, specifically to a thermochromic glass. Background Technology
[0002] With the advancement of building energy conservation and green building concepts, smart dimming glass can dynamically adjust the solar radiation transmittance according to environmental conditions, thereby reducing building cooling / heating energy consumption while improving the comfort of the indoor lighting environment.
[0003] Currently, the most commercially available and researched thermochromic systems mainly fall into three categories: vanadium oxide, hydrogel-based, and organic dye-based. VO2-based thermochromic materials have an intrinsic phase transition temperature of approximately 68°C, which needs to be controlled to the room temperature range through doping, and the visible light transmittance after doping is generally below 70%. While hydrogel-based thermochromic materials offer high color contrast, they suffer from inherent defects such as low-temperature freezing and high-temperature water loss, leading to volume shrinkage and performance degradation with long-term use, and insufficient outdoor weather resistance. Organic dye-based thermochromic materials generally suffer from poor cycle stability and are prone to aging under ultraviolet radiation, making it difficult to meet the service life requirements of more than 10 years for architectural glass.
[0004] Copper-based metal halide coordination polymers, as a new class of inorganic-organic hybrid thermochromic materials, are gradually becoming an important research direction in the field of thermochromism due to their advantages such as high color contrast, precise control of phase transition temperature through ligand design, lead-free and environmentally friendly raw materials, and low cost. These materials achieve a reversible shift in the absorption spectrum by inducing a reversible transition between the Cu-X coordination configuration and the metal-metal interaction through temperature changes, thereby achieving a light-tuning effect.
[0005] However, copper halide coordination polymers are mostly crystalline or cross-linked gel structures. The directionality of the coordination bonds and the rigid framework make them inherently brittle. The elongation at break of pure-phase films is usually less than 2%. They are prone to cracking or even powdering and falling off during bending and temperature cycling, making them unsuitable for independent film formation and difficult to adapt to the high-temperature and high-pressure processing technology of glass lamination. The Cu(I) in the coordination polymer framework is easily oxidized by oxygen and moisture in the environment, leading to the destruction of the coordination structure and irreversible degradation of thermochromic properties. Under humid and hot conditions of 85℃ / 85%RH, performance loss of more than 30% usually occurs within just a few hundred hours, which cannot meet the weather resistance requirements for long-term outdoor use. Summary of the Invention
[0006] This invention aims to at least solve one of the technical problems existing in the prior art, and proposes a laminated glass process that can simultaneously satisfy high optical performance, high mechanical toughness, and high environmental stability for copper(I)-based metal halide thermochromic materials. To this end, this invention proposes: A thermochromic glass includes two glass substrates and a composite film bonded between the two glass substrates by an adhesive film. The method for preparing the composite film includes: Step 1: Under nitrogen protection and light-protected conditions, cuprous iodide and bidentate pyrazolyl ligand are added to an anhydrous mixed solvent and stirred until completely dissolved to obtain a clear and transparent precursor solution; the anhydrous mixed solvent is a mixture of DMF and acetonitrile. Step 2: Coat the precursor liquid uniformly onto the surface of the glass substrate, place it in a sealed solvent-saturated atmosphere, and slowly evaporate the solvent at room temperature to form a continuous coordination polymer gel film in situ. Step 3: Immerse the gel film along with the glass substrate in a mixture of DMF and acetone in a gradient ratio for solvent exchange to remove unreacted raw materials and residual DMF, and then soak it in pure acetone. Step 4: Immerse the gel film after solvent exchange along with the glass substrate in an acetone solution of bidentate pyrazole ligand for 20-60 minutes. After rinsing with pure acetone, place it in an acetone-saturated atmosphere and slowly evaporate the solvent under normal pressure to obtain a dry gel film. Step 5: Immerse the dry gel film along with the glass substrate in the epoxy-thiol composite permeation solution, degas under vacuum to remove air from the pores, and then pressurize to fill the pores of the dry gel with the permeation solution to obtain the composite film precursor after permeation treatment. The epoxy-thiol composite permeate comprises a fluorinated epoxy monomer, a high-refractive-index epoxy monomer, a multifunctional thiol crosslinking agent, and an ultraviolet alkali-generating agent. The high-refractive-index epoxy monomer has a homopolymer refractive index ≥1.55, and the molar ratio of thiol functional groups to epoxy functional groups in the permeate is (1.05~1.2):1. The thiol-epoxy nucleophilic ring-opening click polymerization system is an alkali-catalyzed stepwise polymerization reaction, with no free radical intermediates generated throughout the process, avoiding polymerization termination caused by Cu(I) quenching of free radicals. Simultaneously, the use of a sterically hindered thiol crosslinking agent reduces the probability of coordination side reactions between thiol groups and Cu(I), and a moderate excess of thiol functional groups offsets trace coordination losses. Combined with coordination saturation treatment to seal surface active sites, this ensures the progress of the polymerization reaction. Step 6: Take out the composite film precursor after permeation treatment, clean the excess permeate on the surface, place it in a nitrogen environment and keep it in the dark for at least 30 minutes, and then use ultraviolet light to irradiate both sides to trigger epoxy-thiol ring-opening polymerization to obtain a thermochromic film. Step 7: Vacuum dry the thermochromic composite film to remove residual monomers and trace amounts of solvent, then peel it off from the glass substrate to obtain the composite film.
[0007] One embodiment of the present invention adopts a technical solution to solve its technical problem as follows: In step 1, the molar ratio of cuprous iodide to bidentate pyrazolyl ligand is 1:1 to 1.5:1.
[0008] One embodiment of the present invention adopts the following technical solution to solve its technical problem: In step 1, the volume ratio of DMF to acetonitrile is 1:1 to 3:1.
[0009] One embodiment of the present invention adopts a technical solution to solve its technical problem as follows: In step 1, the bidentate pyrazole ligand is at least one of 1,4-bis(3,5-dimethylpyrazole)butane and 1,6-bis(3,5-dimethylpyrazole)hexane.
[0010] One embodiment of the present invention adopts a technical solution to solve its technical problem as follows: In step 6, the multifunctional thiol crosslinking agent is at least one of trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol tetra(3-mercaptopropionate).
[0011] One embodiment of the present invention adopts a technical solution to solve its technical problem as follows: In step 6, the high refractive index epoxy monomer is at least one of phenyl glycidyl ether and bisphenol A type epoxy resin.
[0012] One embodiment of the present invention adopts a technical solution to solve its technical problem as follows: In step 6, the fluorinated epoxy monomer is at least one of perfluoroalkyl glycidyl ether and trifluoropropyl glycidyl ether.
[0013] The technical solution adopted by one embodiment of the present invention to solve its technical problem is as follows: In step 6, the ultraviolet light alkali-generating agent is an o-nitrobenzyl carbamate photoalkali-generating agent, and the amount added is 2% to 3% of the total mass of the permeate.
[0014] In the composite film, cuprous iodide and bidentate pyrazolyl ligands are first cross-linked through coordination bonds to form a gel network. Then, epoxy-thiol polymer monomers are infiltrated into the pores of the gel network. By triggering photo-alkali production under ultraviolet light, tertiary amines are released, catalyzing the nucleophilic ring-opening polymerization of thiol groups and epoxy, forming a three-dimensional covalently cross-linked organic network in situ. The two networks interweave with each other at the molecular scale without being connected by covalent chemical bonds, and each maintains the independence of its structure and function. This not only fully preserves the thermochromic intrinsic properties of the coordination network, but also gives full play to the mechanical reinforcement and barrier protection functions of the covalent network.
[0015] The gel network, acting as a rigid functional framework, provides structural support, while the three-dimensional covalently cross-linked organic network, as a continuous flexible phase, bears external loads. When the film is subjected to external forces, the coordination bonds in the coordination network can preferentially break as sacrificial bonds to dissipate energy, while the covalent network maintains structural integrity and transmits stress, preventing rapid crack propagation and increasing the film's elongation at break. Simultaneously, the topological constraint of the covalent network limits the volume expansion and contraction of the coordination network during phase transitions, inhibiting the generation and propagation of grain boundary fatigue cracks and significantly improving thermal cycling life. The covalently cross-linked organic network formed by in-situ polymerization encapsulates the gel network at the molecular scale, constructing a continuous water and oxygen barrier, significantly reducing the diffusion rate of water vapor and oxygen into the coordination network, and preventing framework hydrolysis and Cu(I) oxidation. Through coordination saturation treatment, the same pyrazole ligand pre-occupies the unsaturated Cu(I) coordination sites on the surface of the coordination network, reducing the contact between surface active sites and water and oxygen, further inhibiting aging degradation, and reducing the performance degradation rate of the film after 1000 hours of wet heat aging.
[0016] At low temperatures, Cu(I) forms a stable tetrahedral coordination configuration with iodide ions and pyrazole nitrogen atoms. The dd orbital transition energy level difference of the Cu4I4 cluster is relatively large, and the characteristic absorption peak is located in the ultraviolet region, resulting in high transparency of the film in the visible light band. When the temperature rises to the phase transition range, thermal motion causes reversible distortion of the coordination bonds, enhances the Cu-Cu metal-metal interaction, reduces the orbital energy level difference, and redshifts the absorption edge to the visible-near-infrared band, resulting in a darker film color and reduced solar radiation transmittance. When the temperature drops, the coordination configuration spontaneously recovers, and the film returns to a high-transmittance state, achieving passive intelligent dimming. Detailed Implementation
[0017] Unless otherwise stated, the terms used in this invention generally have the meanings commonly understood by those skilled in the art.
[0018] The present invention will now be described in further detail with reference to specific embodiments and data. It should be understood that these embodiments are merely illustrative of the invention and are not intended to limit the scope of the invention in any way.
[0019] In the following embodiments, the various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, apparatus, instruments, equipment, etc., used in the following examples are commercially available.
[0020] The thermochromic glass of this invention comprises two glass substrates and a composite film bonded between the two glass substrates by an adhesive film. The method for preparing the composite film includes: Step 1: Under nitrogen protection, light protection, and room temperature conditions, cuprous iodide and bidentate pyrazolyl ligand are added to an anhydrous mixed solvent at a molar ratio of 1:1 to 1.5:1, and stirred for 30 to 60 minutes until completely dissolved to obtain a clear and transparent precursor solution; the anhydrous mixed solvent is a mixture of DMF and acetonitrile at a volume ratio of 2:1; the bidentate pyrazolyl ligand is at least one of 1,4-di(3,5-dimethylpyrazol)butane and 1,6-di(3,5-dimethylpyrazol)hexane; the concentration of cuprous iodide in the precursor solution is 0.1 to 0.2 mol / L; Step 2: Under nitrogen protection and in the dark, uniformly coat the precursor solution onto the surface of the glass substrate, control the wet film thickness to be 300~500μm, place it in a sealed solvent-saturated atmosphere, and slowly evaporate the solvent at room temperature and pressure for 18~24h to form a continuous coordination polymer gel film in situ; the solvent-saturated atmosphere is a mixed solvent vapor environment formed by DMF and acetonitrile in a volume ratio of 2:1. Step 3: Immerse the gel film along with the glass substrate in a mixture of DMF and acetone in a gradient ratio for solvent exchange. Immerse the film in three solutions with DMF:acetone volume ratios of 3:1, 1:1, and 1:3 for 6-8 hours each, and then immerse it in pure acetone for 12 hours to remove unreacted raw materials and residual DMF. The entire process is carried out at room temperature, under nitrogen protection, and in the dark. Step 4: Immerse the gel film, after solvent exchange, along with the glass substrate, in an acetone solution containing bidentate pyrazolyl ligand at a concentration of 0.05~0.2 mol / L for 20~60 min. After removal, rinse with pure acetone 2~3 times, and then place in an acetone-saturated atmosphere to slowly evaporate the solvent at room temperature and atmospheric pressure for 72~96 h to obtain a dry gel film. The bidentate pyrazolyl ligand is the same type as the ligand used in Step 1. Step 5: Immerse the dry gel film along with the glass substrate in the epoxy-thiol composite permeation solution. First, degas the dry gel film under vacuum conditions of ≤-0.09MPa for 20~40min to remove the air from the pores. Then, pressurize it with nitrogen to 0.2~0.5MPa and maintain the pressure for 2~4h to allow the permeation solution to fill the pores of the dry gel, thus obtaining the composite film precursor after permeation treatment. The epoxy-thiol composite permeate comprises a fluorinated epoxy monomer, a high-refractive-index epoxy monomer, a multifunctional thiol crosslinking agent, and an ultraviolet light alkali-generating agent; the high-refractive-index epoxy monomer has a homopolymer refractive index ≥1.55 and is selected from at least one of phenyl glycidyl ether and bisphenol A type epoxy resin; the fluorinated epoxy monomer is selected from at least one of perfluoroalkyl glycidyl ether and trifluoropropyl glycidyl ether; the multifunctional thiol crosslinking agent is selected from at least one of trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol tetra(3-mercaptopropionate); the molar ratio of thiol functional groups to epoxy functional groups in the permeate is (1.05~1.2):1; the ultraviolet light alkali-generating agent is an o-nitrobenzyl carbamate photoalkali-generating agent, and the addition amount is 2%~3% of the total mass of the permeate; Step 6: Take out the composite film precursor after permeation treatment, clean the excess permeate on the surface, place it in a nitrogen environment and stand in the dark for at least 30 minutes, and then irradiate it on both sides for 40 to 90 seconds with ultraviolet light with a wavelength of 365 nm and a single-sided light intensity of 60~100 mW / cm² to trigger epoxy-thiol ring-opening polymerization and obtain thermochromic composite film. Step 7: After vacuum drying the thermochromic composite film at a temperature of 40~50℃ and a vacuum degree of ≤-0.095MPa for 6~12h to remove residual monomers and trace amounts of solvent, peel it off from the glass substrate to obtain the composite film.
[0021] Based on the above, Embodiment 1 of this application is proposed. The method for preparing the composite thin film in the temperature-changing glass described in this embodiment includes: Step 1: Under nitrogen protection, light protection, and room temperature conditions, weigh 0.12 mol of cuprous iodide and 0.1 mol of 1,6-bis(3,5-dimethylpyrazole)hexane, add them to anhydrous DMF / acetonitrile mixed solvent with a volume ratio of 2:1, and make up to 1 L to obtain a system with a cuprous iodide concentration of 0.12 mol / L; stir magnetically at room temperature for 45 min until the solid is completely dissolved, filter through a 0.22 μm organic filter membrane to obtain a light yellow, clear, and transparent precursor solution; Step 2: Under nitrogen protection and light protection, the precursor solution is uniformly coated onto the surface of the quartz glass substrate using a doctor blade coating method, and the wet film thickness is controlled to be 400 μm. The substrate is placed in a sealed container, and the container is kept with saturated solvent vapor of DMF / acetonitrile at a volume ratio of 2:1. The solvent is slowly evaporated at room temperature and pressure for 20 hours to form a continuous and crack-free coordination polymer gel film in situ. Step 3: Immerse the gel film with substrate sequentially in DMF / acetone mixed solutions with volume ratios of 3:1, 1:1, and 1:3, for 7 hours at each stage, and finally immerse it in pure anhydrous acetone for 12 hours. The entire process is carried out at room temperature, away from light, and under nitrogen protection. Step 4: Immerse the solvent-exchanged gel film in a 0.1 mol / L solution of 1,6-bis(3,5-dimethylpyrazole)hexane-acetone for 40 min; remove it and rinse it three times with pure acetone for 5 min each time to remove free ligands; then place the film in a desiccator filled with acetone saturated vapor and slowly evaporate the solvent at room temperature and pressure for 84 h to obtain a dry gel film with an average thickness of about 100 μm. Step 5: Prepare the epoxy-mercapto composite permeate solution. By mass, the epoxy-mercapto composite permeate solution includes 45 parts of trifluoropropyl glycidyl ether and 55 parts of phenyl glycidyl ether. Add trimethylolpropane tris(3-mercaptopropionate) at a molar ratio of 1.1:1 for mercapto functional groups to epoxy functional groups. Then add 2% of o-nitrobenzyl carbamate photoalkalizing agent by mass of the permeate solution. Stir evenly and degas by ultrasonication. Immerse the dry gel film along with the substrate completely in the epoxy-mercapto composite permeate solution. First, degas under a vacuum of -0.095 MPa for 30 min to remove pore air. Then, pressurize with high-purity nitrogen to 0.3 MPa and maintain the pressure for 3 h to completely fill the pores of the dry gel with the permeate solution, thus obtaining the permeate-treated composite film precursor. Step 6: Remove the permeate-treated composite membrane precursor, gently blot off excess permeate with clean filter paper, and place it in a nitrogen atmosphere away from light for 40 minutes; then irradiate both sides with a 365nm ultraviolet light source, with a single-sided light intensity of 80mW / cm². 2 Each side is irradiated for 30 seconds, with a total irradiation time of 60 seconds, triggering epoxy-thiol ring-opening polymerization to obtain an in-situ composite wet film. Step 7: Place the film in a vacuum drying oven and dry it at 45°C and a vacuum of -0.095MPa for 9 hours to remove residual monomers and trace amounts of solvent; after cooling to room temperature, peel the film off completely from the glass substrate to obtain the composite film.
[0022] Example 2 The difference between Example 2 and Example 1 is as follows: In step 1, the bidentate pyrazolyl ligand used is 1,4-bis(3,5-dimethylpyrazol)butane, the molar ratio of cuprous iodide to ligand is 1.1:1, and the concentration of cuprous iodide in the precursor solution is 0.15 mol / L; In step 4, the ligand solution for coordination saturation treatment is a 0.15 mol / L solution of 1,4-bis(3,5-dimethylpyrazole)butaneacetone, soaked for 30 min; the drying time under normal pressure is 72 h. In step 5, the crosslinking agent used is pentaerythritol tetra(3-mercaptopropionate), with a molar ratio of mercapto to epoxy functional groups of 1.15:1.
[0023] Example 3 The difference between Example 3 and Example 1 is as follows: In step 1, the molar ratio of cuprous iodide to ligand is 1.3:1, and the concentration of cuprous iodide in the precursor solution is 0.18 mol / L; In step 5, the fluorinated epoxy monomer is perfluoroalkyl glycidyl ether, and the high refractive index epoxy monomer is bisphenol A type epoxy resin, with a mass ratio of 5:5; the molar ratio of mercapto to epoxy functional group is 1.2:1, the amount of photoalkali-generating agent added is 3%, and the holding time is 4h.
[0024] Comparative Example The dry gel film obtained in step 4 was used as a control sample.
[0025] The thin film products obtained in Examples 1-3 and the comparative examples were tested as follows, and the test results are shown in Table 1.
[0026] Optical performance testing: The average visible light transmittance of the thin film at 25℃ and 50℃ was measured using an ultraviolet-visible-near-infrared spectrophotometer, and the solar spectral modulation amplitude was calculated.
[0027] Phase transition temperature test: The phase transition temperature is determined by the midpoint of the temperature range with the fastest rate of change in transmittance through variable-temperature ultraviolet spectroscopy.
[0028] Mechanical property testing: The elongation at break of the film was tested using a universal testing machine at a tensile rate of 5 mm / min.
[0029] Moisture and heat resistance test: The film was aged in a constant temperature and humidity chamber at 85℃ / 85%RH for 1000h. The solar spectrum modulation amplitude before and after aging was tested, and the performance degradation rate was calculated.
[0030] Thermal cycling performance test: Thermal cycling test was conducted in the range of -20℃ to 60℃, with each cycle lasting 30 minutes. After 1000 cycles, the performance degradation rate was calculated.
[0031] Performance retention rate: The two sides of the thin film products obtained in Examples 1-3 and the comparative examples were respectively laminated with 0.38 mm thick PVB film and 3 mm thick soda-lime glass, and then hot-pressed at 130°C and 1.2 MPa for 30 min. The solar spectrum modulation amplitude retention rate before and after hot pressing was tested.
[0032] Table 1
[0033] According to the data in Table 1, in Examples 1-3, while fully preserving the thermochromic properties of the copper-based coordination polymer, the elongation at break of the film increased from 1.2% to over 20%, and the performance degradation rate under damp heat aging and thermal cycling decreased from about 40% to less than 6%, thus improving mechanical toughness, environmental stability, and thermo-pressure resistance.
[0034] Of course, the present invention is not limited to the above-described embodiments. Those skilled in the art can make equivalent modifications or substitutions without departing from the spirit of the present invention, and these equivalent modifications and substitutions are all included within the scope defined by the claims of this application.
Claims
1. A thermochromic glass, characterized in that, The composite film comprises two glass substrates and a composite film bonded between the two glass substrates by an adhesive film, wherein the method for preparing the composite film includes: Step 1: Under nitrogen protection and light-protected conditions, cuprous iodide and bidentate pyrazolyl ligand are added to an anhydrous mixed solvent and stirred until completely dissolved to obtain a clear and transparent precursor solution; the anhydrous mixed solvent is a mixture of DMF and acetonitrile. Step 2: Coat the precursor liquid uniformly onto the surface of the glass substrate, place it in a sealed solvent-saturated atmosphere, and slowly evaporate the solvent at room temperature to form a continuous coordination polymer gel film in situ. Step 3: Immerse the gel film along with the glass substrate in a mixture of DMF and acetone in a gradient ratio for solvent exchange to remove unreacted raw materials and residual DMF, and then soak it in pure acetone. Step 4: Immerse the gel film after solvent exchange along with the glass substrate in an acetone solution of bidentate pyrazole ligand for 20-60 minutes. After rinsing with pure acetone, place it in an acetone-saturated atmosphere and slowly evaporate the solvent under normal pressure to obtain a dry gel film. Step 5: Immerse the dry gel film along with the glass substrate in the epoxy-thiol composite permeation solution, degas under vacuum to remove air from the pores, and then pressurize to fill the pores of the dry gel with the permeation solution to obtain the composite film precursor after permeation treatment. The epoxy-thiol composite permeate includes a fluorinated epoxy monomer, a high-refractive-index epoxy monomer, a multifunctional thiol crosslinking agent, and an ultraviolet light alkali-generating agent. The high-refractive-index epoxy monomer has a homopolymer refractive index ≥1.55, and the molar ratio of thiol functional groups to epoxy functional groups in the permeate is (1.05~1.2):
1. Step 6: Take out the composite film precursor after permeation treatment, clean the excess permeate on the surface, place it in a nitrogen environment and keep it in the dark for at least 30 minutes, and then use ultraviolet light to irradiate both sides to trigger epoxy-thiol ring-opening polymerization to obtain a thermochromic film. Step 7: Vacuum dry the thermochromic composite film to remove residual monomers and trace amounts of solvent, then peel it off from the glass substrate to obtain the composite film.
2. The thermochromic glass according to claim 1, characterized in that, In step 1, the molar ratio of cuprous iodide to bidentate pyrazolyl ligand is 1:1 to 1.5:
1.
3. The thermochromic glass according to claim 1, characterized in that, In step 1, the volume ratio of DMF to acetonitrile is 1:1 to 3:
1.
4. The thermochromic glass according to claim 1, characterized in that, In step 1, the bidentate pyrazolyl ligand is at least one of 1,4-bis(3,5-dimethylpyrazol)butane and 1,6-bis(3,5-dimethylpyrazol)hexane.
5. The thermochromic glass according to claim 1, characterized in that, In step 5, the multifunctional thiol crosslinking agent is at least one of trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol tetra(3-mercaptopropionate).
6. The thermochromic glass according to claim 1, characterized in that, In step 5, the high-refractive-index epoxy monomer is at least one of phenyl glycidyl ether and bisphenol A type epoxy resin.
7. The thermochromic glass according to claim 1, characterized in that, In step 5, the fluorinated epoxy monomer is at least one of perfluoroalkyl glycidyl ether and trifluoropropyl glycidyl ether.
8. The thermochromic glass according to claim 1, characterized in that, In step 5, the ultraviolet light alkali-generating agent is an o-nitrobenzyl carbamate photoalkali-generating agent, and the amount added is 2% to 3% of the total mass of the permeate.
